Níveis de cloreto de sódio em rações para frangos de corte - Borges, S. A. (1998)
A trial was carried out using 1,000 day-old chicks to evaluate levels of NaCl (0.30, 0.45, 0.60, 0.75 and 0.90%) in diets. Water and feeding with 20.1 and 18.2% CP, 2, 900 and 2,950 kcal/kg ME respectively for initial and finishing phases were offered ad libitum. High levels of NaCl (0.60, 0.75 and 0.90%) increased the water intake and water:feed ratio during the first 21 days (P<0.05). Whitin the period of 21-42 days only water intake increased (P<0.05). Body weight, feed and water intake, mortality were higher (P<0.05)for males. High levels of NaCl (0.60, 0.75 and 0.90%) increased (P<0.05) body weight, water intake, water:feed ratio and moist litter during the trial. The supplementation of high levels of NaCl increased performance, bur implied in higher litter moisture.